HUBUNGAN FAKTOR DEMOGRAFI DENGAN FAKTOR KENYAMANAN DAN KEAMANAN INVESTOR PASAR MODAL - Erista Widya Kristanti (STIE Perbanas Surabaya, 2012)
Research in the field of behavioral finqnce has not been predominantly done so far. It appears obvious especially, when it is compared with the study of behavior in the financial sector. This is due to the research revealing how the behavior of investors is against the risk of investment and the type of investment that is selected in the money market sector or capital market. This study aims to examine the relationship between demographic factors with the factors of comfortability and security of capital market investors. Research object of this research were the investors who invested their funds in capital markets in Surabaya. Method of data collection is by using questionnaires. With judgment sampling technique (purposive) sampling and snowball sampling, the data were taken up to 84 questionnaires from the respondents in the field and then the validity and reliability of research instruments were done as well as correlation analysis Chi Square Test to answer the problem. Of the 10 the demographic factors gender, ethnicity, oge, marital status, education, occupation, family size, spending per month, investment experience, and frequency of transactions, only the type of work thot hos significant relationship with the factors of psychology, namely comfortability and security.